4-Formylazetidin-2-one as a useful building block for the formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine - Kale, Ajaykumar S.; Sakle, Prathmesh S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
Stereoselective formal synthesis of xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine is described starting from an enantiopure formyl-substituted P-lactam. Grignard reaction of the N-Boc-protected-beta-lactam carbonyl group, followed by further transformations, provides a common intermediate for xylo-(2S,3R,4R)-phytosphingosine and threo-(2S,3S)-sphingosine.
Keywords: azetidin-2-one; beta-lactam; Grignard reaction; Phytosphingosine; Sphingosine

Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis

Practical formal synthesis of D-(+)-biotin from 4-formylazetidin-2-one - Kale, Ajaykumar S.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synthesis-Stuttgart, 2007)
A practical synthesis of (3S,6R)-1,3-dibenzyltetrahydro-1H-furo[3,4-d]imidazole-2,4-dione, an important intermediate in the synthesis of biotin, from 4-formyl-3-mesyloxyazetidin-2-one has been achieved. Acid-catalyzed azetidin-2-one ring opening followed by a one-pot conversion of diamine hydrochloride to a cyclic urea and hydroxymethylene to chloromethylene by triphosgene to obtain (4S,5R)-methyl-1,3-dibenzyl-5-chloromethyl-2-oxoimidazolidine-4-carboxyl ate is the key step in this synthesis.
Keywords: azetidin-2-one; beta-Lactams; cyclization; Lactone; reduction

Stereoselective synthesis of 3-alkylidene/alkylazetidin-2-ones from azetidin-2,3-diones - Tiwari, Dharmendra Kumar; Shaikh, Ashif Y.; Pavase, Laxmikant S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2007)
Azetidin-2,3-diones have been used as synthons for the synthesis of C-3 alkylidene/alkylazetidin-2-ones. Some of the 3-alkylazetidin-2-ones are well known for their cholesterol absorption inhibitor activity. A regio and stereoselective Grignard reaction on a keto group followed by dehydration using PPh3/CCl4 reagent is a key step in this synthesis. Hydrogenation of the 3-alkylideneazetidin-2-ones provided stereoselectively cis-3-alkylazetidin-2-ones in very good yields. (c) 2006 Published by Elsevier Ltd.
Keywords: 3-diones; azetidin-2; azetidin-2-ones; beta-lactam; Grignard reaction

Synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an important intermediate for (3S,4R)-Cisapride - Shirode, Nilesh M.; Likhite, Anjali P.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2008)
An efficient synthesis of (3S,4R)-4-benzylamino-3-methoxypiperidine, an useful intermediate for the chiral synthesis of important drug molecule Cisapride and its analogs, from enantiopure 4-formylazetidin-2-one is described. Synthesis of trans as well as cis isomers of 4-amino-3-methoxypiperidine from 4-formylazetidin-2-one is also achieved in good yield. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: 4-aminopiperidine; azetidin-2-ones; Cisapride; Staudinger reaction; stereoselective synthesis

Efficient formal synthesis of (S)-dapoxetine from enantiopure 3-hydroxy azetidin-2-one - Chincholkar, Pinak M.; Kale, Ajaykumar S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2009)
An efficient formal synthesis of S-(+) dapoxetine starting from 3-hydroxy azetidin-2-one is described. The intermediate (S)-3-(dimethyl amino)-3-phenylpropan-1-ol was synthesized in enantiopure form starting with 3-hydroxy azetidin-2-one in seven steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Azetidin 2 ones; beta-Lactams; Enantioselective synthesis; reduction; Staudinger reaction